Pengelolaan Dana Otonomi Khusus Dalam Upaya Peningkatan Kualitas Pendidikan di Aceh - Wais Alqarni; Aldianto Aldianto; Ahmalian Ahmalian; Aira Riska; Asyiatun Nabila; Widia Zahra; Muhammad Alief (Department of Government Studies, Universitas Syiah Kuala, 2022)
One of the positive impacts of the issuance of Law on the Government of Aceh Number 11 of 2006 is the formation of a strong foundation to form specific regulations under it, and one of them is in the field of education. Strong regulations make Aceh able to get a large fiscal capacity in building education in Aceh. However, at the practical level, the large budget in the field of education has not been directly proportional to the quality of existing education. This study aims to see to what extent the existing special autonomy funds have been able to improve the quality of education in Aceh. Management theory is used as a focus in analyzing this issue. Qualitative research with a strong data-based literature review approach can be accounted for as a method in this research. The result of this research is that the budget allocation management of the special autonomy fund for education in Aceh is still not effective. This is because there are still many activities carried out that have not been fully targeted, weak coordination and cross-sectoral cooperation, lack of long-term quality training. Coupled with the lack of creative programs implemented in supporting the achievement of improving the quality of education in Aceh. Therefore, it is necessary to have proper management and close cooperation between the Aceh government and all relevant stakeholders in order to jointly improve the quality of education in Aceh.